Recovery of possession and owner's money claim under hire purchase law - a critical study / Tan Lee Koon - Tan, Lee Koon (2007)
This paper is mainly concerned with the various pitfalls, from the financier or owner's perspective that can be found in Malaysia's hire-purchase law. These can be found in the Hire Purchase Act 1967 (Act 212) (hereinafter called "the Act") and common law. Since the subject matter i.e., the Malaysian hire-purchase law is quite extensive, this paper shall focus on two areas of our hire-purchase law, mainly, "Recovery of Possession" and "Owner's Money Claim". The object is basically to examine the remedies available to the Owners in event of breaches by the Hirers and the problems associated with such remedies. The researcher has endeavoured to provide a comprehensive analysis of the abovementioned topics of hire-purchase law in all its salient aspects. Further, the researcher hopes that the paper can be used as a work of reference for the busy legal practitioner which will solve the myriad pitfalls of everyday practice. Therefore, the researcher has dealt in some detail with the mechanics of hire-purchase finance. The researcher's own experience has always been that it is easier to absorb legal principles when one is 'hands-on' and familiar with the machinery of their application. This paper shall try to make a comparative analysis of the hire purchase laws of UK, Australia, Singapore and Malaysia in order to expose the weaknesses in our existing hire purchase law. The paper has proposed crucial and important changes albeit drastic to the Malaysian Hire Purchase law.